Effect of grid‐following VSCs on frequency distribution of power grid - Qingyuan Ma; Lei Chen; Luyang Li; Yong Min; Yudan Shi (IET Renewable Power Generation)
Abstract The increasing penetration of grid‐following voltage source converters (GFL‐VSCs) in the power grid has changed the frequency dynamics of the system. GFL‐VSC follows the frequency of the terminal bus using a phase‐locked loop, therefore it does not establish the frequency in the same manner as a synchronous generator. However, previous research has demonstrated that GFL‐VSC without additional frequency controls not only tracks the terminal frequency during the system dynamic process bus also has an influence on it, and derives the relationship between GFL‐VSC and terminal frequency through a simplified model. This paper further derives a more generic relationship considering the influences of q‐axis current and grid voltage amplitude variation, which were ignored in previous research. The relationship has proven to be effective and valid. Several influencing factors are analysed to describe the ability to modify terminal frequency. Then the effect of GFL‐VSCs on the frequency distribution of power grid is studied. The frequency divider formula is improved by incorporating the relationship, which provides a frequency estimation formula applicable for system with multiple GFL‐VSCs. Two system‐level simulations verify the conclusion and related influencing factors are analysed.